2008
DOI: 10.1140/epja/i2008-10634-2
|View full text |Cite
|
Sign up to set email alerts
|

Transverse-mass effective temperature in heavy-ion collisions from AGS to SPS

Abstract: Abstract. Transverse-mass spectra in Au + Au and Pb + Pb collisions in the incident energy range from 2A to 160A GeV are analyzed within the model of 3-fluid dynamics (3FD). It is shown that the dynamical description of freeze-out, accepted in this model, naturally explains the incident-energy behavior of the inverse-slope parameters of these spectra observed in experiment. The simultaneous reproduction of the inverse slopes of all considered particles (p, π and K) suggests that these particles belong to the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The step-like structure in the energy dependence of the inverse slope parameter of the transverse mass spectra was obtained within the hydrodynamical model by introduction of a rapid change of the freeze-out conditions at low SPS energies [69]. However, this assumption does not explain the increase of the inverse slope parameter suggested by the RHIC results.…”
Section: Alternative Approachesmentioning
confidence: 95%
“…The step-like structure in the energy dependence of the inverse slope parameter of the transverse mass spectra was obtained within the hydrodynamical model by introduction of a rapid change of the freeze-out conditions at low SPS energies [69]. However, this assumption does not explain the increase of the inverse slope parameter suggested by the RHIC results.…”
Section: Alternative Approachesmentioning
confidence: 95%
“…In Refs. [20,21] it was shown that dynamical description of the freeze-out [22,23], accepted in the 3FD model, naturally explains the step-like behavior of inverse-slope parameters even without any deconfinement transition in the EoS. This freeze-out dynamics, effectively resulting in a pattern similar to that of the dynamic liquid-gas transition, differs from conventionally used freeze-out schemes.…”
Section: Introductionmentioning
confidence: 97%
“…If there is a phase transition the mean transverse mass excitation function should show a flattening because of the mixed phase region where the temperature of the system stays constant. However, recently, it has been suggested in a 3-fluid model with a hadron gas equation of state that the characteristic steplike-behaviour of the mean transverse mass in dependence of the incident beam energy might be a relic of the freeze-out treatment in a hydrodynamic calculation and may not be a unique sign of the transition to the QGP [11].…”
Section: Introductionmentioning
confidence: 99%